Impact of Eye Prosthetic on State of Depression: A Literature Review - Christian Andrew Darian Sianipar (Sriwijaya Journal of Ophthalmology, 2021)
Depression is a significant comorbid and a risk factor for mortality in the general population. There are many things that can affect someone’s mental health thus rendering the said individual into contracting depression. One of these many things observed is the loss of one’s eyes. It is hypothesized that self-esteem comes from how one perceive himself or herself and losing a dominant organ whose function is to be a media of interpersonal communication would mess someone’s self image. This shattered image paved way to depression. Identifying certain risk factors and signs could help physician to better manage patients with loss of eyes especially those who are utilizing eye prosthesis.